Edukasi Kurma pada Ibu Hamil untuk Peningkatan Kadar Haemoglobin pada Kehamilan di Klinik Permata Bunda Tahun 2025 - Jumiati, Jumiati; Susanti, Sri; Marliana, Lina (Universitas Respati Indonesia, 2025)
Anemia among pregnant women is a significant factor contributing to maternal and infant mortality, preterm birth, and stunting if not promptly addressed (Indonesian Health Profile, 2023). One preventive measure is meeting nutritional needs through the consumption of dates, which are rich in iron—approximately 13.7 mg per 100 grams (Satuhu, 2010). The role of midwives in managing anemia, as stated in Midwifery Care Standard No. 6, includes prevention, detection, treatment, and referral of anemia cases in pregnant women. An educational outreach on the benefits of dates was conducted at the Permata Bunda Clinic to increase pregnant women’s knowledge about improving hemoglobin (Hb) levels through date consumption. Among the 39 participants, the average pre-test score was 63.62, which increased to 77.08 in the post-test, showing an average gain of 20.28 points. The standard deviation also decreased from 23.77 to 12.41, indicating that participants’ knowledge became more consistent after the session. These findings demonstrate that the educational intervention on date consumption effectively enhanced the understanding of expectant mothers regarding the need to sustain adequate hemoglobin levels throughout the gestational period, contributing to the prevention of anemia, stunting, and obstetric complications.